Motivación de logro en educación física y capacidades motrices en alumnos de una institución educativa pública del distrito de Bellavista - Arista Huaco, Manuel Jesús (2010)
This investigation is about achievement motivation for learning in Physical Education and motor skills in high school students from fifth a State Educational Institution Bellavista - Callao District. Its design is descriptive and correlation study, the group of 140 students between 15 and 18 years was given the motivation test of 37 items, Achievement Motivation in Physical Education Test also an observation form on motor abilities of 7 items where the results revealed: Motivation in Physical Education has a positive trend by 85%, as motor skills by 65% and there was a positive correlation (r = 76.2%) between the physical abilities and motivation, these results are discussed in relation to the transmission of information by the teacher to improve student's ability, intrinsic motivation and performance.